Determination of Essential and Non-essential Elements in Moringa stenopetala Leaves and Flowers Using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) in Dawuro Zone, Southern Ethiopia - Solomon Ragasa; Kusse Gudishe (Journal of Science and Inclusive Development, 2020)
This study aimed at determining concentration levels of essential elements (K, Ca, Fe, Mn, Zn, Cu, Ni) and non-essential elements (Pb, and Cd) present in leaves and flowers of Moringa stenopetala. Dry ash digestion method was deployed. The absorption intensity of the elements in Moringa stenopetala leaves and flowers were recorded by inductively coupled plasma optical emission spectroscopy. Results indicate that the mean concentration of the elements in Moringa stenopetala leave samples are (in mg/kg): Ca (5,713.86 - 6621.14), K (27,587.10 - 28,315.40), Pb (0.73 - 0.81), Zn (41.17 - 47.00), Cd (0.05 - 0.83), Cu (2.41 - 4.74), Ni (0.54 - 0.80), Mn (26.75 - 26.92), Fe (61.05 - 65.30). Moreover, the mean concentration of the elements in Moringa stenopetala flower samples are (in mg/kg): Ca (2,796.97 - 3,028.67), K (28,358.30 - 36,008.60), Pb (0.54 - 0.68), Zn (24.48 - 30.66), Cd (ND - 0.03), Cu (1.83 - 4.69), Ni (0.53- 0.61), Mn (12.37- 14.52) and Fe (108.97 - 114.03). Results show that the levels of elements are higher in the leaves than in the flowers, except K. The levels of most elements analyzed in M. stenopetala plant samples of this study were compared well with those reported for different medicinal plants from some other parts of the world and standards set by FAO/WHO. Leaves of M. stenopetala, commonly consumed part in Southern Ethiopia, showed appreciable mineral contents and thus are good source of essential nutrients while toxic elements are found less than permissible limits set by FAO/WHO and are safe for human consumption.